Desempenho de fundos de pensão sob a ótica das boas práticas de governança corporativa e da auditoria independente - Sabrina Amélia de Lima e Silva (2018)
This research proposes to measure performance for the largest Brazilian pension funds, with data from 2012 to 2017, through actuarial and financial indicators. It also seeks to investigate the association between corporate governance, independent auditing and the performance of these entities. The demographic transition in Brazil, growing deficits and even cases of corruption in pension funds are factors that may raise questions about closed private pension plans. The study uses data from 50 pension funds that hold more than 80% of total market investments and cover about 50% of the pension fund population. A quantitative study was developed using techniques such as Data Envelopment Analysis, Spearman Correlation, Principal Component Analysis, Granges Causality and Multiple Panel Data Regression. The thesis consists of three articles. In article 1, the performance of Brazilian pension funds with financial and actuarial indicators was measured, establishing a ranking for the entities. It was possible to discuss the determinants of this performance, highlighting the composition of the mass of retirees and pensioners of the plans. There is evidence of low efficiency in Brazilian pension funds. In article 2, a quality index of corporate governance was created and a causal relationship between the index and the fund performance in Brazil was verified. Finally, in article 3, the characteristics of the independent audit were assessed as relevant to the performance of the pension funds, especially the auditor's specialization and the size of the audit firm. The results of this research bring contributions to the discussion of important characteristics in the measurement of the performance of pension funds and what variables of corporate governance and independent auditing that can influence this performance. This research is relevant in a Brazilian context of public pension reform and in an international context of complementary pension growth.